2019
DOI: 10.1186/s40798-019-0209-9
|View full text |Cite
|
Sign up to set email alerts
|

Inter-rater Reliability in Assessing Exercise Fidelity for the Injury Prevention Exercise Programme Knee Control in Youth Football Players

Abstract: Background To receive maximum benefits from injury prevention exercise programmes (IPEP) such as Knee Control , players need to perform the exercises as prescribed. But, exercise fidelity in IPEPs is seldom evaluated. We developed a checklist to assess exercise fidelity in the Knee Control IPEP, and the primary aim was to evaluate its inter-rater reliability. The secondary aim was to study Knee Control exercise fideli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 24 publications
(33 reference statements)
0
23
0
Order By: Relevance
“…When used in rehabilitation progression should be made individually, based on each patient's neuromuscular control and movement quality 2 . In the IPEPs used in team sports, the neuromuscular training is usually team-based and progressed for the whole team at the same time for practical reasons 66,92,[147][148] . During all exercises, the quality of the movements should be emphasised 2 .…”
Section: Neuromuscular Trainingmentioning
confidence: 99%
See 4 more Smart Citations
“…When used in rehabilitation progression should be made individually, based on each patient's neuromuscular control and movement quality 2 . In the IPEPs used in team sports, the neuromuscular training is usually team-based and progressed for the whole team at the same time for practical reasons 66,92,[147][148] . During all exercises, the quality of the movements should be emphasised 2 .…”
Section: Neuromuscular Trainingmentioning
confidence: 99%
“…A study of female youth football reported that some players did not concentrate upon the execution of the exercises 157 . Recently, the exercise fidelity in football teams using the Knee Control IPEP has been studied using a checklist 92 . Overall, only 48% of the observed exercises were performed correctly, which may reduce the preventive effectiveness of the IPEP 92 .…”
Section: Implementation Of Injury Prevention Exercise Programmesmentioning
confidence: 99%
See 3 more Smart Citations